Use of the permanent strain rate to analyze the effect of superheavy vehicles on pavements: Field validation. (September 2021) - Pérez-González, Erdrick; Bilodeau, Jean-Pascal; Doré, Guy
Abstract: In the development and maintenance of hydroelectric, mining, or oil industries, it is necessary to transport elements with non-conventional load magnitudes. The approval or rejection of the road network's use by vehicles carrying this type of load is conditioned on the pavement's capacity to withstand these special loading conditions without suffering considerable damage. The quantification of permanent deformation in granular materials is one of the critical parameters to consider. The authors have recently proposed a model for analyzing the effect of superheavy loads based on the rate of permanent deformation in granular materials. The model has been developed from laboratory tests, and its applicability has been demonstrated with numerical model results. In this paper, field measurements were used to validate the proposed model. Field stress measurements were used to predict the probable ranges for plastic strains using the model, and these results were compared with the plastic strains measured in the field. Consistency between predicted ranges and field measurements was observed in five cases of superheavy vehicles, evaluated at different speeds and climatic conditions. An adjustment factor for the field stresses is introduced to improve the model prediction, and typical values for the parameters of the deformation rate model are given in the paper.